The Impact of Vaccination Frequency on COVID-19 Public Health Outcomes: A Model-Based Analysis - Lin Yuan; Madison Stoddard; Sharanya Sarkar; Debra van Egeren; Shruthi Mangalaganesh; Ryan P. Nolan; Michael S. Rogers; Greg Hather; Laura F. White; Arijit Chakravarty (Vaccines)
Background: While the rapid deployment of SARS-CoV-2 vaccines had a significant impact on the ongoing COVID-19 pandemic, rapid viral immune evasion and waning neutralizing antibody titers have degraded vaccine efficacy. Nevertheless, vaccine manufacturers and public health authorities have a number of options at their disposal to maximize the benefits of vaccination. In particular, the effect of booster schedules on vaccine performance bears further study. Methods: To better understand the effect of booster schedules on vaccine performance, we used an agent-based modeling framework and a population pharmacokinetic model to simulate the impact of boosting frequency on the durability of vaccine protection against infection and severe acute disease. Results: Our work suggests that repeated dosing at frequent intervals (three or more times a year) may offset the degradation of vaccine efficacy, preserving the utility of vaccines in managing the ongoing pandemic. Conclusions: Given the practical significance of potential improvements in vaccine utility, clinical research to better understand the effects of repeated vaccination would be highly impactful. These findings are particularly relevant as public health authorities worldwide have reduced the frequency of boosters to once a year or less.